Breakfast Skipping, Body Composition, and Cardiometabolic Risk: A Systematic Review and Meta‐Analysis of Randomized Trials. Issue 6 (18th April 2020) - Bonnet, Jonathan P.; Cardel, Michelle I.; Cellini, Jaqueline; Hu, Frank B.; Guasch‐Ferré, Marta
Abstract : Objective: The objective of this study was to evaluate the effect of skipping breakfast on body composition and cardiometabolic risk factors. Methods: This study conducted a systematic review and meta‐analysis of randomized controlled trials (RCTs) evaluating breakfast skipping compared with breakfast consumption. Inclusion criteria included age ≥ 18, intervention duration ≥ 4 weeks,  ≥ 7 participants per group, and ≥ 1 body composition measure. Random‐effects meta‐analyses of the effect of breakfast skipping on body composition and cardiometabolic risk factors were performed. Results: Seven RCTs ( n  = 425 participants) with an average duration of 8.6 weeks were included. Compared with breakfast consumption, breakfast skipping significantly reduced body weight (weighted mean difference [WMD] = −0.54 kg [95% CI: −1.05 to −0.03], P  = 0.04, I 2  = 21.4%). Percent body fat was reported in 5 studies and was not significantly different between breakfast skippers and consumers. Three studies reported on low‐density lipoprotein cholesterol (LDL), which was increased in breakfast skippers as compared with breakfast consumers (WMD = 9.24 mg/dL [95% CI: 2.18 to 16.30], P  = 0.01). Breakfast skipping did not lead to significant differences in blood pressure, total cholesterol, high‐density lipoprotein (HDL) cholesterol, triglycerides, C‐reactive protein, insulin, fasting glucose, leptin, homeostatic model assessment of insulin resistance, or ghrelin. Conclusions: Breakfast skipping may have a modest impact on weight loss and may increase LDL in the short term. Further studies are needed to provide additional insight into the effects of breakfast skipping.